The Pattern of Antibiotic Prescription and Antimicrobial Resistance of Gut Flora Escherichia coli at Aisyiyah Hospital, Bojonegoro - Hidayah, Ana Nurlaili; Hasmono, Didik; Thayyib, Muqoddar; Kuntaman, K (Folia Medica Indonesiana, 2020)
Antimicrobial resistance (AMR) is the failure of antibiotic to kill bacteria and becomes ineffective in therapeutic purpose. The AMR bacteria is a major health problem worldwide and Indonesia is not exception. AMR is increased by two factors, higher antibiotic use and low compliance in infection control and prevention. WHO has recommended 7 bacterial indicators as point of view in surveillance, one of these bacteria is Escherichia coli. This study aimed to analyze the correlation between antibiotic use and resistance pattern of gut flora Escherichia coli. The study was conducted at Aisyiyah Hospital, Bojonegoro from June to October 2017. Total 101 patients from internal medicine and surgery department in this hospital were included in this study. Bacterial gut flora were tested against 12 antibiotics by disk diffusion test at the Department of Clinical Microbiology, Universitas Airlangga.. The results showed that the highest quantity of antibiotic use in internal medicine service was cefepime (40,50 DDD) and the highest resistance rate was ciprofloxacin, whereas in the surgical service it was ceftriaxone (132,75 DDD) with the highest E. coli resistance to amoxicillin-clavulanic acid. The antibiotics use has significant correlation against E. coli resistance on cefotaxime (p=0.046), ceftazidime (p=0.046), ceftriaxone (p=0.017), aztreonam (p=0.024), and cefepime (p=0.010).